Predominant Cerebellar Volume Loss as a Neuroradiologic Feature of Pediatric Respiratory Chain Defects - Scaglia, Fernando (AJNR Am J Neuroradiol, 2005)
BACKGROUND AND PURPOSE: Predominant cerebellar involvement has not been previously reported as a common neuroradiologic feature in pediatric mitochondrial cytopathies. Here we report the neuroradiologic findings of predominant cerebellar volume loss in children with various mitochondrial disorders. METHODS: A retrospective analysis of the medical records of 400 consecutive patients referred for evaluation of mitochondrial encephalomyopathies was performed. In 113 cases, definite diagnosis of mitochondrial disease was based on the modified adult criteria that include clinical, histologic, biochemical, functional, molecular, and metabolic parameters. RESULTS: Predominant cerebellar volume loss with progressive cerebellar atrophy and, less often, cerebellar hypoplasia were found in a heterogeneous group of patients with mitochondrial disease that consisted of four patients with complex I deficiency; four patients with multiple respiratory chain deficiencies; two patients with combined complex I + III and II + III deficiencies, including one patient with partial coenzyme Q(10) deficiency; three patients with complex II deficiency; two patients with complex IV deficiency; one patient with mitochondrial neurogastrointestinal encephalomyopathy; and two patients with mitochondrial encephalomyopathy, lactic acidosis, and strokes. CONCLUSION: Our retrospective study shows that isolated or predominant cerebellar involvement can be found in various respiratory chain defects or mitochondrial disorders expanding the classical neuroradiologic findings observed in mitochondrial encephalomyopathies. The diagnostic workup in patients with neuromuscular features whose brain MR imaging exhibits cerebellar volume loss should include the evaluation for mitochondrial encephalomyopathies.